Effective termination of atrial fibrillation by SK channel inhibition is associated with a sudden organization of fibrillatory conduction. Issue 11 (3rd June 2021) - Gatta, Giulia; Sobota, Vladimir; Citerni, Carlotta; Diness, Jonas Goldin; Sørensen, Ulrik S; Jespersen, Thomas; Bentzen, Bo Hjorth; Zeemering, Stef; Kuiper, Marion; Verheule, Sander; Schotten, Ulrich; van Hunnik, Arne
Abstract: Aims: Pharmacological termination of atrial fibrillation (AF) remains a challenge due to limited efficacy and potential ventricular proarrhythmic effects of antiarrhythmic drugs. SK channels are proposed as atrial-specific targets in the treatment of AF. Here, we investigated the effects of the new SK channel inhibitor AP14145. Methods and results: Eight goats were implanted with pericardial electrodes for induction of AF (30 days). In an open-chest study, the atrial conduction velocity (CV) and effective refractory period (ERP) were measured during pacing. High-density mapping of both atrial free-walls was performed during AF and conduction properties were assessed. All measurements were performed at baseline and during AP14145 infusion [10 mg/kg/h ( n  = 1) or 20 mg/kg/h ( n  = 6)]. At an infusion rate of 20 mg/kg/h, AF terminated in five of six goats. AP14145 profoundly increased ERP and reduced CV during pacing. AP14145 increased spatiotemporal instability of conduction at short pacing cycle lengths. Atrial fibrillation cycle length and pathlength (AF cycle length × CV) underwent a strong dose-dependent prolongation. Conduction velocity during AF remained unchanged and conduction patterns remained complex until the last seconds before AF termination, during which a sudden and profound organization of fibrillatory conduction occurred. Conclusion: AP14145 provided a successful therapy for termination of persistent AF in goats. During AF, AP14145 caused an ERP and AF cycle length prolongation. AP14145 slowed CV during fast pacing but did not lead to a further decrease during AF. Termination of AF was preceded by an abrupt organization of AF with a decline in the number of fibrillation waves.